(3GdaUhd GdegeI aj eYQaI CUhd GdCFeIs - (3eMeO Hf GdMSf Hf Ydj GdYGedj , GdMQ GdYGedj,J (B1104 (3g` s
(3ChdgG (B:s
(3hHYO jbhd GdabjQ Edi Gddg eMeO deG YdehG ef RjGI faY GdcdjGJ s
(3BNQgG (B:s
(3dcf ehQO GdQhGjJjf eNJda GP GdChdi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI KGfjIZes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B321 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B204s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B195s
Keywords: (3abg GdePGgH GdCNQis